PENELUSURAN PENENTU RETURN SAHAM - Faidh, Muhamad Iran; Yulianti, Yulianti; Widowati, Sri Yuni; Santoso, Aprih (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
Abstract. This study aims to determine the Current Ratio (CR), Earning Per Share (EPS), Price Earning Ratio (PER), Debt To Equity Ratio (DER), and systematic risk of stock returns in 2015-2018. the population in this study is 25 food and beverage manufacturing companies listed on Bursa Efek Indonesia.The sampling technique used ispurposive sampling, with a total of 11 companies meeting the sample criteriaData analysis techniques used multiple linear regression analysis. The result showed Current Ratio (CR), Earning Per Share (EPS), Price Earning Ratio (PER), Debt To Equity Ratio (DER) has no effect on stock returns, while systematic risk affects Stock Return. Abstrak. Penelitian ini bertujuan untuk mengetahui Current Ratio (CR), Earning Per Share (EPS), Price Earning Ratio (PER), Debt To Equity Ratio (DER), dan risiko sistematis return saham tahun 2015-2018. Populasi dalam penelitian ini adalah 25 perusahaan manufaktur makanan dan minuman yang terdaftar di Bursa Efek Indonesia. Teknik pengambilan sampel yang digunakan adalah purposive sampling, dengan jumlah 11 perusahaan yang memenuhi kriteria sampel. Teknik analisis data menggunakan analisis regresi linier berganda. Hasil penelitian menunjukkan Current Ratio (CR), Earning Per Share (EPS), Price Earning Ratio (PER), Debt To Equity Ratio (DER) tidak berpengaruh terhadap return saham, sedangkan risiko sistematis berpengaruh terhadap return saham.